2004
DOI: 10.1080/02571862.2004.10635026
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Ambic 1 and Bray 1 extractable phosphorus in some South African arable soils

Abstract: South African analytical laboratories use different extractants for P in soils of which the most important are Bray 1, Ambic 1, Bray 2, Truog and Olsen. The fertilizer industry prefers to use Bray 1 extractions for fertilization recommendations and the ARC-Grain Crops Institute, Ambic 1 extractions for calibration research. Therefore it became necessary to establish relationships between the P extracted by the two methods in specific soils and if possible to relate differences in these relationships to soil pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The highest AMBIC extractable P concentrations (> 20 mg·kg -1 ) were measured (in decreasing order) in the WTR 12 > 5 > 2 ≈ 9 (Table 2). Typical AMBIC P concentrations for South African soils have been reported to range between 0.3 and 15.3 mg·kg -1 (Schmidt et al, 2004), suggesting that the WTR with high P concentrations may be beneficial from an agronomic perspective and that the land application on P-deficient soils may be of some potential value.…”
Section: Chemical Characteristicsmentioning
confidence: 99%
“…The highest AMBIC extractable P concentrations (> 20 mg·kg -1 ) were measured (in decreasing order) in the WTR 12 > 5 > 2 ≈ 9 (Table 2). Typical AMBIC P concentrations for South African soils have been reported to range between 0.3 and 15.3 mg·kg -1 (Schmidt et al, 2004), suggesting that the WTR with high P concentrations may be beneficial from an agronomic perspective and that the land application on P-deficient soils may be of some potential value.…”
Section: Chemical Characteristicsmentioning
confidence: 99%
“…In addition, a modified version of the ISFEI (IP) method was used to determine the 'P status' of modal profiles during the compiling of land type maps (Land Type Survey Staff, 1985). Although much work has been done locally and internationally to compare various P extraction methods, much of this work has been restricted to unpublished reports (Schmidt et al, 2004).…”
Section: Labile Pmentioning
confidence: 99%
“…After a study comparing BP1 and AP results from 12 localities in South Africa, Schmidt et al (2004) reported the following relationship using linear regression analysis: BP1 = 1.23 × AP + 3.82…”
Section: Labile Pmentioning
confidence: 99%
“…The equations were then used to derive extractable P concentrations (mg kg-I) or quantities (kg ha-I ) required in the top 150 mm soil for either 90% or 95% grain yield. All of these threshold values were converted to either equivalent Ambic I or Bray I values using the equations of Schmidt et al (2004). The extractable P threshold values for both Ambic I and Bray I were then subjected to simple and mUltiple regression analyses with soil properties.…”
Section: Data Processingmentioning
confidence: 99%
“…Plant Grond 2007, 24(1) Institute for extractable P according to the Ambic I method (Van der Merwe, Johnson, Ras & Schultz, 1981; The Nonaffiliated Soil Analysis Work Committee, 1990), while only some of the samples from each locality were analysed for extractable P according to the Bray I method (Bray & Kurtz, 1945; The Non-affiliated Soil Analysis Work Committee, 1990). However, sufficient samples were analysed with both extractants in order to establish simple regression equations for the conversion of Ambic 1 and Bray I values from one another (Schmidt, Adriaanse & Du Preez, 2004). Other analyses with standard methods (The Non-affiliated Soil Analysis Work Committee, 1990) carried out on these soil samples (114) 373 (63) 582 (98) 684 (116) 477 (81) 727 (123) 925 (156) were particle size distribution (pipette and sieve), pH (M KCI), exchangeable acidity (M KCI), organic C (WalkleyBlack) and exchangeable Ca, Mg, K and Na (Ambic I).…”
Section: Soil Sampling and Analysismentioning
confidence: 99%